1986
DOI: 10.1002/eji.1830161015
|View full text |Cite
|
Sign up to set email alerts
|

Mice naturally tolerant to C5 have T cells that suppress the response to this antigen

Abstract: We examined whether C5-sufficient mice which are naturally tolerant to this antigen have suppressor T cells to C5 humoral immune response. Two congenic strains of mice B10.D2 (NSN) and B10.D2 (OSN) differing only in the presence or absence of C5 were used. Irradiated (760 rds) sufficient hosts were reconstituted with a nonadherent spleen cell suspension from either sufficient or deficient mice or a mixture of both. Hemolytic C5 levels were assayed. Sufficient spleen cells appeared to prevent the drop of C5 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There have been numerous demonstrations, as early as the 1970s and 1980s, that self-reactive cells exist in normal, non-autoimmune mice [59,[77][78][79][80][81][82][83][84][85]. Many of these demonstrations involved removing the reactive cells from their normal environment, implying the existence in that environment of peripheral control mechanisms.…”
Section: Self-tolerance To Mrbc Maintained By Regulatory T Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…There have been numerous demonstrations, as early as the 1970s and 1980s, that self-reactive cells exist in normal, non-autoimmune mice [59,[77][78][79][80][81][82][83][84][85]. Many of these demonstrations involved removing the reactive cells from their normal environment, implying the existence in that environment of peripheral control mechanisms.…”
Section: Self-tolerance To Mrbc Maintained By Regulatory T Cellsmentioning
confidence: 98%
“…Many of these demonstrations involved removing the reactive cells from their normal environment, implying the existence in that environment of peripheral control mechanisms. Regulatory T-cell populations have been demonstrated in many of these models to abrogate the development of autoimmune diabetes [77,78], thyroiditis, [79], experimental allergic encephalomyelitis [EAE; 80,81], gastritis and orchitis [59,82,83], nephritis [84], autoantibody responses to the C5 component of complement [85], and autoantibody production by DNA-specific B-cell lines [86]. Some of these studies identified the cells responsible for control as CD8 ?…”
Section: Self-tolerance To Mrbc Maintained By Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In T and B cell mixing experiments from the two strains, it was shown that B cells from either strain had the potential for anti-C5 reactivity and that the tolerance to C5 was strictly T cell dependent. Evidence for a population of T cells able to inhibit a response to C5 was demonstrated by Cairns et al (1986). It was found that non-adherent spleen cells (naSC) from C5~ animals, upon adoptive transfer to sublethally irradiated C5"^ animals, were able to make an antibody response to C5, resulting in a transient, but significant, reduction in C5 levels.…”
Section: Role Of Antigen In the Generation Of Regulatory T Cells And mentioning
confidence: 99%
“…Given that T cell anergy is a reversible state (Mueller et al 1989) this explanation cannot entirely be dismissed. However in the dominant tolerance in which antigen specificity is known, for example in the thymus transplantation experiments of Coutinho et al (1993) and Zamoyska et al (1989) and in the C5 experiments of Cairns et al (1986), it is difficult to refute the view that the T cells that mediate dominant tolerance are specific for the "tolerated" antigen. While in principle the observed antigen specificity could arise through the recognition, by the regulatory T cells, of the TCR idiotypes on the regulated cells the existence of such a mechanism would impose an enormous extra burden on the intrathymic selection of the T cell repertoire.…”
Section: Suppressor Epitopesmentioning
confidence: 99%